Spatial and temporal characteristics of air pollutant emissions in Thessaloniki, Greece: investigation of emission abatement measures - Tsilingiridis, George; Zachariadis, Theodoros; Samaras, Zissis (My University, 2002)
The paper presents new detailed emissions inventory for the Greater Area of Thessaloniki, northern Greece, which incorporates a large amount of data on the polluting anthropogenic and biogenic activities in the region, including the location of all individual point, line and area sources along with their daily, weekly and monthly profiles and activity rates. The emission estimate followed both the bottom-up and the top-down approaches. Apart from the base year calculations, scenario estimates are provided for the base year, intended to show the maximum possible benefit of abatement measures and for the future, in order to estimate the evolution of air pollutant emissions in relation to structural changes and land planning. Air pollutant emissions were calculated for an area of 5120 km2 at two different spatial resolutions (1×1 km2 and 2×2 km2) in order to support air quality simulations in the region. The resulting spatially allocated emission database, which also incorporates elevation and land use data, constitutes a clear improvement in comparison to existing emissions inventories of the area, and the procedure followed can be considered as a ‘best practice’ guide for developers of urban emissions inventories.
Keywords: Emission; Inventory; Spatial analysis; Temporal variation; Abatement measures; Thessaloniki, Greece